2019
DOI: 10.1016/j.apsusc.2018.11.210
|View full text |Cite
|
Sign up to set email alerts
|

Improved laser induced damage thresholds of Ar ion implanted fused silica at different ion fluences

Abstract: Qing (2019) Improved laser induced damage thresholds of Ar ion implanted fused silica at different ion fluences. Applied Surface Science, 471. pp. 786-794.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 31 publications
(40 reference statements)
0
3
0
1
Order By: Relevance
“…This effect can be explained by surface densifying of SiO 2 and silicate glasses at ions implantation [6][7][8], that shortens the development of damaging process. Molecular mechanism of compaction induced by ions consists in reduction of angles of Si−O−Si with formation of 3-and 4-membered siloxane rings [9].…”
Section: Resultsmentioning
confidence: 99%
“…This effect can be explained by surface densifying of SiO 2 and silicate glasses at ions implantation [6][7][8], that shortens the development of damaging process. Molecular mechanism of compaction induced by ions consists in reduction of angles of Si−O−Si with formation of 3-and 4-membered siloxane rings [9].…”
Section: Resultsmentioning
confidence: 99%
“…Заметно, что в генерация АЭ из имплантированного слоя значительно более кратковременна, чем с нетронутой поверхности. Этот эффект можно объяснить уплотнением поверхности SiO 2 и силикатных стекол при внедрении ионов [6][7][8], что сокращает развитие процесса повреждения. Молекулярный механизм наведенной ионами компактизации заключается в уменьшении углов Si−O−Si с образованием 3-и 4-членных силоксановых колец [9].…”
Section: результаты и обсуждениеunclassified
“…e noncontact processing model enables IBSE technique not to introduce defects such as pollution and scratches, so as to achieve the goal of manufacturing optical elements with high surface quality and damage threshold. By studying the surface modification, Li found that IBSE can effectively improve the surface state of fused silica, and the damage threshold could reach more than 15 J/cm 2 [12,13]. Liao detected fused silica surface polished by IBSE technique with high-resolution methods such as atomic force microscope and found that no defects generate on the surface, which proved the effectiveness of the technique [14].…”
Section: Introductionmentioning
confidence: 99%